Promotion of Pt/CeO2 catalyst by hydrogen treatment for low-temperature CO oxidation - Jan, Asif; Shin, Jisu; Ahn, Junsung; Yang, Sungeun; Yoon, Kyung Joong; Son, Ji-Won; Kim, Hyoungchul; Lee, Jong-Ho; Ji, Ho-Il (ROYAL SOC CHEMISTRY, 2019)
Low temperature CO oxidation reaction is known to be facilitated over platinum supported on a reducible cerium oxide. Pt species act as binding sites for reactant CO molecules, and oxygen vacancies on surface of cerium oxide atomically activate the reactant O-2 molecules. However, the impacts of size of Pt species and concentration of oxygen vacancy at the surface of cerium oxide on the CO oxidation reaction have not been clearly distinguished, thereby various diverse approaches have been suggested to date. Here using the co-precipitation method we have prepared pure ceria support and infiltrated it with Pt solution to obtain 0.5 atomic% Pt supported on cerium oxide catalyst, and then systematically varied the size of Pt from single atom to similar to 1.7 nm sized nanoparticles and oxygen vacancy concentration at surface of cerium oxide by controlling the heat-treatment conditions, which are temperature and oxygen partial pressure. It is found that Pt nanoparticles in range of 1-1.7 nm achieve 100% of CO oxidation reaction at similar to 100 degrees C lower temperature compared to Pt single atom owing to the facile adsorption of CO but weaker binding strength between Pt and CO molecules, and the oxygen vacancy in the vicinity of Pt accelerates CO oxidation below 150 degrees C. Based on this understanding, we show that a simple hydrogen reduction at 550 degrees C for the single atom Pt supported on CeO2 catalyst induces the formation of highly dispersed Pt nanoparticles with size of 1.7 +/- 0.2 nm and the higher concentration of surface oxygen vacancies simultaneously, enabling 100% conversion from CO to CO2 at 200 degrees C as well as 16% conversion even at 150 degrees C owing to the synergistic effects of Pt nanoparticles and oxygen vacancies.
Keywords: WATER-GAS-SHIFT; METAL-SUPPORT INTERACTION; SINGLE-ATOM; OXYGEN; CERIA; CEO2; PLATINUM; OXIDE; ROOM; PD